Analysis of histology-agnostic targets among soft tissue and bone sarcomas in the AACR GENIE database - Pestana, Roberto Carmagnani; Serrano, César (Frontiers in Oncology, 2023)
Background: The development of novel therapies for patients with sarcoma is challenging due to the rarity and diversity of these mesenchymal neoplasms. Hence, histology-agnostic approvals can be of particular interest for the treatment of patients with soft tissue and bone sarcoma. Material and Methods: We queried the American Association for Cancer Research (AACR) Project Genomics Evidence Neoplasia Information Exchange (GENIE) database Cohort v12.0-Public to investigate the prevalence of currently Food and Drug Administration (FDA)-approved and other potentially actionable histology-agnostic alterations in patients with soft tissue and bone sarcoma. Targets were identified by a literature review by the authors. Results are presented for each cohort identified in the GENIE database, namely: (1) soft tissue sarcoma (STS), (2) gastrointestinal stromal tumor (GIST), (3) bone sarcoma, (4) uterine sarcoma, and (5) breast sarcoma. Results: We identified 7,512 samples of 6,955 patients with sarcoma in the AAACR GENIE database v12.0-Public. Molecular alterations that could lead to the clinical use of a currently approved histology-agnostic therapy were identified in 2.1% of sarcomas (2.6% STS, 1.3% GIST, 1.4% bone, 2.7% uterine, and 0% breast). In addition, 2.9% of patients could be eligible for future histology-agnostic approvals. These specific mutations, fusions, and amplifications occurred in multiple histotypes in all cohorts. Conclusions: Exploring a public large-scale genomic database, we identified that 5% of patients with sarcoma could be eligible for current histology-agnostic FDA-approved drugs or future potential histology-agnostic indications. These actionable alterations were present in a wide variety of histologies in soft tissue and bone sarcomas, highlighting that next-generation sequencing can be considered for patients with advanced sarcoma to guide treatment strategies.